The Influence of Social Media Marketing Activities (SMMas) on Purchase Decisions is Mediated by Electronic Word of Mouth (E-WOM) and Perceived Value in Compass Shoe Brands - Abdullah Sufyan, Bagja; Madiawati, Putu Nina; Widodo, Arry (International Journal Labs, 2025)
This study examines the influence of Social Media Marketing Activities (SMMAs) on purchase decisions, mediated by Electronic Word of Mouth (E-WOM) and perceived value, in the context of Compass as one of the leading local sneaker brands in Indonesia. The rapid growth of the creative economy in Indonesia and the dominance of digital platforms in consumer behavior make understanding the role of social media in shaping purchasing decisions even more important. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to analyze data from 384 respondents who knew about the existence of Compass on social media. The results show that Social Media Marketing Activities (SMMAs) have a significant effect on Electronic Word of Mouth (E-WOM) and perceived value, where interactive content and following trends are the main drivers of consumer engagement. Furthermore, Electronic Word of Mouth (E-WOM) has been proven to have a significant mediating effect between Social Media Marketing Activities (SMMAs) and perceived value by strengthening consumer trust and perception of brands. Perceived value is also an important determinant in purchasing decisions, including functional, emotional, and social dimensions. While Compass already has a strong level of digital engagement, it has been found that there are gaps in functional value and price perceptions that are areas for strategic improvement. This research contributes theoretically by integrating the consumer behavior framework with the concept of digital marketing, as well as providing practical implications for fashion brands in utilizing social media to strengthen consumer decision-making pathways in the competitive sneakers market.